Cubic spline interpolation for petroleum engineering data - Abdul Karim, S.A. (Hikari Ltd., 2014)
Interpolation and fitting the data to produce the interpolating curves or fitting curves are important in Oil and Gas (O&G) industry. Data interpolation is useful for scientific visualization for data interpretation. One of the efficient methods for data interpolation is cubic spline function. In this paper two types of cubic spline will be used for data interpolation. The first one is cubic spline interpolation with C2 continuity. Meanwhile the second spline is Piecewise Cubic Hermite Spline (PCHIP) with C1 continuity. Numerical comparison between both cubic splines and linear splines will be discussed in details. From all numerical results, it was indicated that cubic spline gives good results. Â© 2014 Samsul Ariffin Abdul Karim et al.